A study of sheath brown rot disease at different field in Sawah Sempang, Merlimau, Malacca / Mohamad Anuar Zulkefli and Mohd Zafri Ab Wahab - Zulkefli, Mohamad Anuar; Ab Wahab, Mohd Zafri (Faculty of Plantation and Agrotechnology, 2018)
Rice (Oryza sativa) is the staple food and a source of income for farmers in Malaysia. Generally, sheath brown rot disease reduces rice production and cause economic loss to the farmer and grower at Merlimau, Melaka. In facts, sheath brown rot disease cause by Pseudomonas fuscovaginae. The symptom show in initially it become yellowish and lower leaf sheath usually turn light or dark brown at the next stage of infection, the whole leaf sheath becomes necrotic. In this study, data on disease incidence and disease severity were collected and analyzed. Meanwhile, soil pH, meteorology data (Rain, relative humidity, wind, temperature), farmers practices information were also obtained. The incidence level (%) of sheath brown rot disease at several fields in Kampung Sempang, Merlimau, Malacca. The study shows that Field 2 is the highest percent occurrence for incidence level of disease with (48.14%) followed by Field 3 (35.52%) and the lowest percentage by Field 1 (23.06%). For severity level of sheath brown rot disease, Field 2 showed the highest percent occurrence for severity which is (42.44%) followed by Field 3 with (20.56%) and Field 1 (16.83%). This percentage of incidence and severity was recorded at paddy field Kampung Sempang, Merlimau, Malacca. The occurrence factor of sheath brown rot on disease incidence and severity was possibly due to water management, rate and timing of fertilizer application and also the environmental factor.